Panorama: Catelli Wins North Finals - Unknown (Daily Express)
Catelli All Stars emerged as the winner of the Panorama North finals, snatching victory away from WITCO Desperadoes and ISCOTT Casablanca. These three steelbands have made it quite clear that the Panorama national finals will be a straight fight between them. The Panorama East zonal finals were won by International Trust Nu-Tones. This puts Nu-Tones within striking distance of the national title.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Trinidad and Tobago